(untitled) (Revista Española de Fisiología, 1973)
Clofibrate (CF) administered for one month to PTU-treatcd rats íncreased thyroid uptake, PBI131 serie levels, thyroxin synthesis and thryroid stable iodine concentration. In another experiment, which was carried out during two months, CF normalized thyroid uptake and thyroxin synthesis in rats having taken PTU for the first month, and raised the thyroid iodine over the control valúes. Nevertheless the PTU-goiter in both experiments was not modified by CF.